Enhancing Food Security Through Systematic African Women Empowerment in South Africa - Masuku, Mfundo Mandla; Garutsa, Tendayi (Richtmann Publishing, 2021)
This paper critically argues how the gender and development approach influences food security for women. A critical literature review analysis was conducted using peer-reviewed publications and grey literature from relevant organisations. Sources from 1993 to 2020 were manually selected from Sabinet and Google Scholar using a purposive and snowball approach and 69 articles were analysed. Findings indicated that although the Gender and Development approach is useful in understanding the issue of food security within the South African context, a post-development feminist approach can guide policy frameworks that recognise differences in women when addressing food insecurity, to enhance women empowerment. This paper recommends that gender and food security issues ought to be conceptualised and understood in a multidimensional sense, using various determinants which include consumption, income, poverty and human development. Received: 21 September 2021 / Accepted: 25 October 2021 / Published: 5 November 2021